Efecto del Fotoperiodo sobre la Producción y Reproducción de Alpacas en la Provincia de Cotopaxi. - Ortega Pasato, Luis Alberto (2018)
This research was carried out in the Province of Cotopaxi, in the communities of APHUA, ACCHI VAQUERÍA and UTC (CEASA) because they have the most significant number of animals and the experimental centre because of it is a part of a research project; the objective was to determine the effect of the photoperiod on production and reproduction in alpacas. Direct observation, management, and review of records of the communities under study, as well as the meteorological centers of the province, were used as part of the methodology. The data were taken from May 2017 to April 2018 and categorized by the two stations Ecuador has (winter-summer), and grouped by the established parameters of the investigation. The results obtained from the research, in the number of light hours studied in the winter-summer season, there is greater light hours in summer concerning winter, the Apahua community recorded lower light hours, 65.27 in summer and 56.26 in winter, it is the community with fewer light hours among the three. There is a higher volume of fiber production in kg in the winter season, with an average of 2.87 kilograms per alpaca and in summer 2.61 kg. The highest values in pregnancy rate occurred in summer with almost twice as many cases compared to winter, while in the number of births there is a higher percentage in winter, just before the end of the season, with respect to the weights of the offspring there is no significant difference, since nutrition more conditions this phenomenon than with respect to the photoperiod.